Pelvic obliquity and measurement of hip displacement in children with cerebral palsy. (2nd November 2018) - Hägglund, Gunnar; Goldring, Mikael; Hermanson, Maria; Rodby-Bousquet, Elisabet
Abstract : Background and purpose — Pelvic obliquity, common in individuals with cerebral palsy (CP), changes the muscle force vector on the hip joint and probably affects the risk of hip dislocation. We evaluated a new method for measurement of hip displacement in CP that takes the pelvic obliquity into account: the pelvic adjusted migration percentage (PAMP). Children and methods — From the Swedish surveillance program for cerebral palsy (CPUP), the first pelvic radiograph of 268 children <18 years in southern Sweden during a 3-year period were evaluated. Pelvic obliquity, PAMP, and the migration percentage (MP) were measured. 50 radiographs were randomly selected for analysis of interrater reliability by three raters using the intraclass correlation coefficient (ICC). The correlations between PAMP/MP and pelvic obliquity were analyzed with Pearson correlation coefficients. Results — The interrater reliability for all 3 measurements was high (ICCs 0.88–0.97). The correlation between the high side of the pelvic obliquity and the difference between right and left hip displacement was higher for PAMP (r = 0.70) than for MP (r = 0.41). Interpretation — The new PAMP measurement showed high interrater reliability and a higher correlation with pelvic obliquity than MP. We suggest the use of PAMP at least in hips with a pelvic obliquity exceeding 5°.